Cone-beam breast CT-guided surface location facilitates breast-conserving surgery in breast cancer patients with extensive calcifications: A pilot study - Sun, Ya; He, Ni; Ye, Feng; Zhou, Chunyan; Wu, Yaopan; Xie, Chuanmiao; Tang, Jun (Frontiers in Surgery, 2023)
Background: Extensive malignant-appearing calcifications has been traditionally considered as a contraindication for breast-conserving surgery. The evaluation of calcifications largely depends on mammogram, which is limited by tissue superimposition and unable to reveal spatial information of extensive calcifications. Three-dimensional imaging modality is needed to reveal the architecture of extensive calcifications. In the present study, a novel technique of cone-beam breast CT guided surface location was investigated to facilitate breast-conserving surgery in breast cancer patients with mammographic extensive malignant calcifications. Methods: Biopsy-proved early breast cancer patients with mammographic extensive malignant-appearing calcifications were included. The patient would be considered suitable for breast-conserving surgery if spatial segmental distribution of calcifications is found by 3D images of cone-beam breast CT. Then the margins of calcifications were located in contrast-enhanced cone-beam breast CT images. Next, skin markers were located using radiopaque materials, and cone-beam breast CT were re-performed to confirm the accuracy of surface location. During breast-conserving surgery, lumpectomy was performed according previous surface location, and intraoperative specimen X-ray was applied to doublecheck the entire lesion is removed. Margin assessment was made both intraoperative frozen section and postoperative pathology examination. Results: From May 2019 to Jun 2022, eleven eligible breast cancer patients in our institution were included. Breast-conserving surgery was performed successfully in all patients by using the surface location approach mentioned before. All patients achieved negative margins and satisfied cosmetic results. Conclusions: This study proved the feasibility of cone-beam breast CT guided surface location for facilitating breast-conserving surgery in breast cancer patients with mammographic extensive malignant calcifications.